Forward production of Υ mesons in pp collisions at √s=7 and 8 TeV - Aaij, Roel; Aquines Gutiérrez, Osvaldo; D'Argent, Philippe; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; et al. (Journal of high energy physics, 2015)
The production of Υ mesons in pp collisions at $$ \sqrt{s}=7 $$and 8 TeV is studied with the LHCb detector using data samples corresponding to an integrated luminosity of 1 fb−1 and 2 fb−1 respectively. The production cross-sections and ratios of cross-sections are measured as functions of the meson transverse momentum p and rapidity y, for p < 30 GeV/c and 2.0 < y < 4.5.